Injection-induced Gluteus Muscle Contractures: Diagnosis With the "Reverse Ober Test" and Surgical Management. Issue 2 (March 2015) - Scully, MAJ William F.; White, Klane K.; Song, Kit M.; Mosca, Vincent S.
Abstract : Background: Adoption rates are increasing in the United States and other developed countries. A large proportion of adopted children have been found to have unsuspected medical diagnoses, including orthopedic problems. One condition, termed injection-induced gluteus maximus contracture, has been previously described in several case series and can be difficult to diagnose if unfamiliar with this condition. By reviewing the etiology and pathoanatomy of this problem, as well as the typical examination findings, including the near-pathognomonic-positive "reverse Ober test, " treating providers will be better prepared to recognize and properly treat this condition. Methods: This is a retrospective review of 4 patients treated at our institution for injection-induced gluteus maximus contracture. Patient history, physical examination findings, and treatment outcomes were recorded. All had undergone surgical treatment through a longitudinal incision along the posterior margin of the iliotibial band, with division of thickened, contracted gluteus tissue down to the ischial tuberosity. Results: All 4 of the patients were adopted from orphanages in developing countries. Chief complaints of the patients varied, but physical examination findings were very consistent. Three of the 4 patients had undergone rotational osteotomies for presumed femoral retroversion before their diagnosis and treatment for injection-induced gluteus maximus contracture. All patients had concave, atrophic buttock contours and numerous punctate buttock scars. All walked with an out-toed gait and had marked apparent femoral retroversion. Each patient was found to have full hip adduction when the hip was extended but a hip abduction contracture when the hip was flexed. This finding of increasing abduction as an extended/adducted hip is flexed to 90 degrees is described as a positive "reverse Ober test." After surgical treatment, all hips could adduct to neutral from full extension to full flexion. Conclusions: Although common in some countries, such as Russia and China, injection-induced gluteus muscle contractures are seldom seen in the United States and other developed countries. Diagnosis of this condition can be difficult leading to inappropriate treatment. Knowledge of the clinical presentation typical of a gluteus contracture and of the pathognomonic finding of a "reverse Ober test" can facilitate an effective surgical procedure to correct the associated functional impairment. Level of Evidence: Level IV: retrospective case series.